PENGARUH KARAKTERISTIK INDIVIDU PENGALAMAN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA UKM CV. RATU PATNI - Fitriandari, Mahayanti; Wijaya, I Kadek Arya; Meryawan, I Wayan; Nindia Putri, Cokorda Istri Agung Vera (Universitas Ngurah Rai, 2025)
Small and Medium Enterprises (SMEs) are widespread in Indonesia, particularly in Bali. The SME CV. Ratu Patni Denpasar is facing low work productivity, which is caused by weak individual characteristics, lack of work experience, and an unsupportive work environment. The aim of this research is to determine the simultaneous and partial influence of individual characteristics, work experience, and work environment on employee productivity at the SME CV. Ratu Patni. This research uses a quantitative approach involving 34 respondents who were used as the research sample. The sampling technique used in this research is saturation sampling, and data were collected through the distribution of questionnaires. The data analysis techniques used in this research are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Determination Coefficient, t-test, and F-test. Based on the results of the research, there is a positive and significant influence both simultaneously and partially between individual characteristics, work experience, and work environment on employee productivity. Approaches to improving work productivity from this study can be implemented by paying attention to work experience and also considering individual characteristics and the work environment, especially in SMEs similar to CV. Ratu Patni.